Democracia y guerra civil: ciudadanía y establecimiento de la paz en Costa de Marfil (2020)
The civil war in Côte d’Ivoire presents unique features with respect to the causes of civil wars and the nature of peace processes in West Africa. It is a conflict largely driven by concrete political and social grievances over citizenship. In addition, it is marked by a significant effort by the belligerents to take ownership of the peace process and negotiate directly. This article traces the civil war to the politicization of citizenship and ethnicity during the democratization process. It argues that the peace agreements engineered by the international community failed to end the conflict largely because they relied heavily on traditional peace formulas and paid insufficient attention to the underlying issue of citizenship. In contrast, the peace agreement forged by Ivorians has been relatively successful because it directly addressed the citizenship issue and restored domestic ownership of the peace process. This article focuses on the peace process and the intrinsic relation between citizenship and progress toward peace in Côte d’Ivoire. In addition, it connects the discourse on democracy in Africa with the salient issue of citizenship and underscores the fluidity of citizenship and democracy in African politics.